The needs and challenges of international teaching assistants (ITAs) in the U.S. classroom and the effective and professional training strategies for ITAs - Wang, Xinran (Kansas State University, 2022)
The United States has been the most popular destination for international students to pursue their academic goals due to its quality of the higher education system, welcoming culture, and relatively open labor market after they graduate (Zong & Batalova, 2018). Meanwhile, the international students have brought a diverse culture to higher education and contributed to the U.S. economy. It is common for U.S. universities to hire international graduate students as teaching or research assistants to teach fundamental courses for undergraduates, which releases the financial pressure on the universities and faculties’ teaching load. However, international teaching assistants (ITAs) face various difficulties in teaching and learning. The researcher, as an ITA, has overcome the dilemma of language barriers, pedagogy methods, and social-cultural issues during the years of graduate study and training. This study contains the researcher’s individual experience and aims to explore the needs and challenges of the ITA group in American university classrooms. For instance, lacking communication capacity and pedagogical strategies, adapting the differences of education systems between home countries and the U.S., balancing the research and teaching tasks. According to the interviews with several ITA participants, this study summarized the similarities and differences of their teaching needs and difficulties in the classroom, including their pressure on curriculum and research, limited assistance from departments, faculty members, and other organizations on the campus, especially transferring remote teaching and lacking mental support during the COVID-19 pandemic. The study collected participants’ thoughts and suggestions on teaching reflection, time management, and professional development to support the ITA group and related training program on linguistic, pedagogy, and social-cultural aspects.
Keywords: International teaching assistants (ITAs); Challenges; Professional development; Teaching training strategies